3+4(3x+6)+3=5+2(2x+5)-3x

Simple and best practice solution for 3+4(3x+6)+3=5+2(2x+5)-3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3+4(3x+6)+3=5+2(2x+5)-3x equation:


Simplifying
3 + 4(3x + 6) + 3 = 5 + 2(2x + 5) + -3x

Reorder the terms:
3 + 4(6 + 3x) + 3 = 5 + 2(2x + 5) + -3x
3 + (6 * 4 + 3x * 4) + 3 = 5 + 2(2x + 5) + -3x
3 + (24 + 12x) + 3 = 5 + 2(2x + 5) + -3x

Reorder the terms:
3 + 24 + 3 + 12x = 5 + 2(2x + 5) + -3x

Combine like terms: 3 + 24 = 27
27 + 3 + 12x = 5 + 2(2x + 5) + -3x

Combine like terms: 27 + 3 = 30
30 + 12x = 5 + 2(2x + 5) + -3x

Reorder the terms:
30 + 12x = 5 + 2(5 + 2x) + -3x
30 + 12x = 5 + (5 * 2 + 2x * 2) + -3x
30 + 12x = 5 + (10 + 4x) + -3x

Combine like terms: 5 + 10 = 15
30 + 12x = 15 + 4x + -3x

Combine like terms: 4x + -3x = 1x
30 + 12x = 15 + 1x

Solving
30 + 12x = 15 + 1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
30 + 12x + -1x = 15 + 1x + -1x

Combine like terms: 12x + -1x = 11x
30 + 11x = 15 + 1x + -1x

Combine like terms: 1x + -1x = 0
30 + 11x = 15 + 0
30 + 11x = 15

Add '-30' to each side of the equation.
30 + -30 + 11x = 15 + -30

Combine like terms: 30 + -30 = 0
0 + 11x = 15 + -30
11x = 15 + -30

Combine like terms: 15 + -30 = -15
11x = -15

Divide each side by '11'.
x = -1.363636364

Simplifying
x = -1.363636364

See similar equations:

| -8x+2=-38 | | 2c^2=13c+7 | | 4z-10=-46 | | 2x^3-11x^2=-5x | | -7+5y=-17 | | -4x+30=18 | | 340-45x=40+5x | | -4.5w=0.375(7-4w) | | -8x-40=0 | | 4z-10=-42 | | 0.4(5x+10)=1.7-(x+2) | | 3w+9=-6 | | -76-24= | | 235+(-150)= | | 9x=-37 | | x+11=5x+12-(7x-2) | | 3x+15=2x+4x-6 | | 6x-9=7x-1 | | (X^3+x^2-3)(x^3-2x+3)=5 | | 3x-9=-8+4x | | 5(4x-3)-3(4x)=15+2(x-13) | | 3x-100=450 | | x=(x+17) | | 9p-29=-92+2p | | 0=-x^2+2 | | 9(y-7)=5y-23 | | 2x+8(5)=x(-28)+2 | | 2x-(9x+3)=6-7x | | x^2+11x+37= | | 12x^2-27=0 | | y=.5x+5 | | 4x^3-8x=0 |

Equations solver categories